ä»¥é©¬å†…åˆ©åˆä¸äºŒæ ¡äºŒå¹´çº§å¦ç”Ÿâ€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€çš„ æŽŒæ¡æƒ…å†µåˆ†æž - (F13110021), Falentika; ., Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The aim of this research is to know the different and the similarities ofthe words â€œBuâ€ and â€œMei (You)â€ and also to know the understanding condition of the students of Immanuel II Junior High School Grade Eight about words â€œBuâ€ and â€œMei (You)â€.This research used literature study as the method to understandÂ and analyze the similarities and differences of the words â€œBuâ€ and â€œMei (You)â€and also used the test method to test the understanding of the students of Immanuel II Junior High School Grade Eight. The results of the research obtained show that â€œBuâ€ and â€œMei (You)â€can be used in the front of the verbs, the adjectives and groups of verbs-objects. However, there is a certain condition which the use of â€œBuâ€ and â€œMei (You)â€ has different meaning. Furthermore, the test results indicate that the total percentages of the students accuracy in the type of questions â€˜Fill in the blankâ€™ about â€œBuâ€ and â€œMei (You)â€are 39.57% and 65.56%. Meanwhile, the total percentages of the students accuracy in the type of questions â€˜multiple choicesâ€™ â€œBuâ€ and â€œMei (You)â€are 41.80% and 35.83%. In conclusion, the results show the negative attitude towards the students mastery in the use of the words â€œBuâ€ and â€œMei (You)â€. Keywords : â€œBuâ€ , â€œMei (You)â€, the condition of studentâ€™s understandingæ‘˜è¦ï¼šä¸ºäº†è§£â€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€çš„å¼‚åŒç‚¹åŠä»¥é©¬å†…åˆ©åˆä¸äºŒæ ¡äºŒå¹´çº§å¦ç”Ÿå¯¹â€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€çš„æŽŒæ¡æƒ…å†µï¼Œæœ¬æ–‡ç”¨æ–‡çŒ®ç ”ç©¶æ³•åˆ†æžâ€œä¸â€å’Œ â€œæ²¡ï¼ˆæœ‰ï¼‰â€çš„å¼‚åŒç‚¹ï¼Œä½¿ç”¨æµ‹éªŒæ³•å¯¹å¦ç”Ÿè¿›è¡Œæµ‹è¯•ã€‚ç ”ç©¶ç»“æžœå¾—çŸ¥ï¼Œâ€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€éƒ½å¯ä»¥ç”¨åœ¨åŠ¨è¯ã€å½¢å®¹è¯å’ŒåŠ¨å®¾è¯ç»„å‰ï¼Œä½†æœ‰ä½ç½®ä¸åŒçš„æƒ…å†µï¼Œå³ä½¿ä½ç½®ç›¸åŒæ„æ€ä¹Ÿä¸ç›¸åŒã€‚æµ‹è¯•ç»“æžœå¾—çŸ¥ï¼Œä»¥é©¬å†…åˆ©åˆä¸äºŒæ ¡äºŒå¹´çº§å¦ç”Ÿâ€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€å¡«ç©ºéƒ¨åˆ†çš„æ€»æ£ç¡®çŽ‡åˆ†åˆ«ä¸ºï¼š39,57% å’Œ65,56%ã€‚é€‰æ‹©æ£ç¡®ä½ç½®éƒ¨åˆ†çš„æ€»æ£ç¡®çŽ‡åˆ†åˆ«ä¸ºï¼š41,80%å’Œ35,83%ï¼Œè¿™è¯´æ˜Žè¯¥æ ¡çš„å¦ç”Ÿå¯¹â€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€çš„æŽŒæ¡æƒ…å†µä¸å¤ªä¹è§‚ã€‚é€šè¿‡è¿™é¡¹ç ”ç©¶ï¼Œç¬”è€…å¸Œæœ›èƒ½å¸®åŠ©å¦ç”Ÿæ›´å¥½åœ°æŽŒæ¡â€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€çš„ç”¨æ³•ï¼Œå¹¶ä¸ºæ±‰è¯æ•™å¸ˆé€‰æ‹©â€œä¸â€å’Œâ€œæ²¡ï¼ˆæœ‰ï¼‰â€çš„æ•™å¦æ³•æä¾›ä¾æ®ã€‚ å…³é”®è¯ï¼šâ€œä¸â€ï¼›â€œæ²¡ï¼ˆæœ‰ï¼‰â€ï¼›æŽŒæ¡æƒ…å†µ